Happiness, stress and social loans in school communities: a possible path for environmental education - Trovarelli, Rachel Andriollo; Alves, Denise Maria Gândara (Revista Hipótese, 2018)
This work researched happiness among members of school communities of public schools who attended a course of Environmental Education/Sustainable Schools. A perception questionnaire about happiness, stress level and social bonds in the schools was applied. The results show that even under stress the number of people with self-declared happiness is high and there is solidarity, evaluated by the support and friendship perceived, allowing theoretical reflections on its transformative potential.
Keywords: Happiness; Environmental Education; Sustainable Schools